Registration of 'Loma' Hard Red Winter Wheat. Issue 3 (15th June 2017) - Bruckner, P. L.; Berg, J. E.; Kephart, K. D.; Stougaard, R. N.; Pradhan, G. P.; Lamb, P. F.; Miller, J. H.; Briar, S. S.; Chen, C.; Nash, D. L.; Holen, D. L.; Cook, J. P.; et al.
Abstract : 'Loma' (Reg. No. CV‐1126, PI 680576) hard red winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in 2016. Loma was derived from the cross 'Yellowstone'//MTS0112/MTS0125. It was developed using a modified bulk breeding method and selected as an F6:7 head row. Loma was tested under the experimental number MTS1224 in Montana yield trials from 2012 to 2016. Like the predominant cultivar Yellowstone, Loma is a high‐yielding, winter‐hardy wheat cultivar with medium to late maturity, medium to high grain protein concentration, and acceptable milling and baking quality characteristics. Loma was released for its excellent performance in winter wheat production environments of north‐central Montana, reduced plant height, and its semisolid stem, which provides some host plant resistance to wheat stem sawfly ( Cephus cinctus Nort.).